People's Republic of China-Hong Kong Special Administrative Region : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2008)
This report on the Observance of Standards and Codes on the Financial Action Task Force (FATF) on money laundering (ML) recommendations discusses antimoney laundering and combating the financing of terrorism for the People's Republic of China (PRC). Hong Kong has a good legal structure to combat ML and terrorist financing (TF). The laundering of drug proceeds has declined and is increasingly derived from trafficking for domestic use. Hong Kong has implemented the provisions of the Vienna and Palermo Conventions, but shortcomings exist in implementation of the Terrorist Financing Convention.